A retrospective analysis of acute poisoning cases admitted to a tertiary care hospital in South India - Anandabaskar, Nishanthi; Murugan, Reveda; Selvaraj, Nitya; Jayaraman, Mohanasundaram; Rajamohammad, Meher Ali; Kagne, Rajendrakumar Nivaratirao (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Acute poisoning is a medical emergency and a global public health problem. The poisoning pattern varies across countries and even between different regions within a country. The aim of this was to explore the demographic, etiological, and clinical characteristics of acute poisoning cases admitted to a tertiary care hospital in Puducherry, South India. Methods: This was a retrospective hospital record based study of acute poisoning cases admitted to our hospital during the period from January 2015 to December 2017. The patients’ demographic, etiological and clinical characteristics were analyzed. Results: Of the total of 275 cases of acute poisoning, majority of them were in the age group of 21- 30 years (32%) and were females (58.5%). Most of the cases were suicidal in nature (75.3%). Majority of the patients consumed a single poisonous agent (92.7%) and the route of poisoning was oral in all of them. Majority of the patients (56.7%) reached the hospital within 2 hours of exposure to the poison with median duration of hospital stay of 2 days, and mortality of 2.9%. Majority of the suicidal poisonings were associated with abuse of insecticides (39.4%), rodenticides (19.7%) and plant seeds (14.4%); whereas the accidental poisonings were mostly due to household agents (79.1%). Conclusions: Our study shows that the majority of the poisoning cases occurred with a single poisonous agent consumed orally, for suicidal purposes in young age group and women. Pesticides and plant seeds were commonly abused for committing suicides and household agents dominated the list of causes for accidental poisoning.